The Emerging Role of RNA Modifications in DNA Double-Strand Break Repair - Jimeno, Sonia; Balestra, Fernando R.; Huertas, Pablo (Frontiers in Molecular Biosciences, 2021)
The correct repair of DNA double strand breaks is essential for maintaining the stability of the genome, thus for the survival and fitness of any living organism. Indeed, the repair of these lesions is a complicated affair, in which several pathways compete for the DNA ends in a complex balance. Thus, the fine tuning of the DNA double strand break repair pathway choice relies on different regulatory layers that respond to environmental cues. Among those different tiers of regulation, RNA modifications have just emerged as a promising field.